The Arab Spring – Implications for the Russian Federation - Stopczyński, Andrzej (International Studies. Interdisciplinary Political and Cultural Journal, 2018)
The Arab Spring led to a major transformation of political systems of the region’s most countries; an increase in the significance of radical Islam in the political life; a degradation of the security environment. In addition, changes in the region’s economy cannot be overlooked. The events connected with the Arab Spring gave the Russian Federation completely new challenges. The country has to yet again define the character of its relations with Muslim countries and adapt its foreign policy to the new post-revolutionary reality. The Arab Spring also represents a challenge for Russia in its internal affairs.